Assessment the quality of removal the smear layer using by rotary tool with zero taper (LLC "Endo Press", 2020)
Smear layer is created by rotary and hand instrumentation. This layer closes dentin tubules and reduces the effect of irrigating solutions, the quality of obturation and outcome of endodontic treatment. The aim of this study was to assess the quality of removal the smear layer with the traditional way of chemo-mechanical instrumentation and with addition of a new instrument XP-endo Finisher. This in vitro study included 40 single-rooted extracted premolars, аnd 20 molars which were separated into 3 groups - «A», «B» and «С». All groups were preparing using NiTi instruments ProFile, NaOCl 3%, EDTA 17%. In groups «B» and «С» the smear layer was removed using XP-endo Finisher. In SEM we received results based on Hulsmann criteria in each canal third (coronal, middle and apical), which were analyzed. Application of XP-endo Finisher removed the smear layer from root canal walls in all segments.